2020
DOI: 10.3390/cancers12010136
|View full text |Cite
|
Sign up to set email alerts
|

Proline-Dependent Induction of Apoptosis in Oral Squamous Cell Carcinoma (OSCC)—The Effect of Celecoxib

Abstract: Background: Oral squamous cell carcinoma remains a significant worldwide public health challenge, associated with high morbidity and mortality. Treatment of this type of cancer lacks effective medication. Moreover, there are very few specific biomarkers that are useful in early diagnosis or treatment optimisation. Proline metabolism may prove to be of importance in the search for new treatment modalities. Methods: To evaluate the significance of proline metabolism in the development of oral cancer, proline con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Indeed, COX-2 inhibitors, such as celecoxib, have widespread anticancer activities and can induce apoptosis in cancer cells 78 . Of note, preliminary indications in oral squamous cell carcinoma suggest that celecoxib treatment increases levels of PRODH1, although it has yet to be established whether such an increase contributes to celecoxibmediated suppression of cell growth and viability 79 . In agreement with its role as tumor suppressor gene, reduced expression of PRODH1 has been reported in several cancers, with more consistent downregulation observed in renal cancers and cancers arising from the digestive tract 64,71,76,[79][80][81] .…”
Section: The Ambivalent Role Of Prodh In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, COX-2 inhibitors, such as celecoxib, have widespread anticancer activities and can induce apoptosis in cancer cells 78 . Of note, preliminary indications in oral squamous cell carcinoma suggest that celecoxib treatment increases levels of PRODH1, although it has yet to be established whether such an increase contributes to celecoxibmediated suppression of cell growth and viability 79 . In agreement with its role as tumor suppressor gene, reduced expression of PRODH1 has been reported in several cancers, with more consistent downregulation observed in renal cancers and cancers arising from the digestive tract 64,71,76,[79][80][81] .…”
Section: The Ambivalent Role Of Prodh In Cancermentioning
confidence: 99%
“…Preliminary data suggest that inhibiting proline biosynthesis enhances sensitivity of colorectal cancer cells and hepatocellular carcinoma cells to standard of care chemotherapy agents 5-FU and sorafenib, respectively 86,104 . On the other hand, PRODH has been implicated in cell death induced by p53-inducing DNAdamaging drugs 69 and to contribute to anti-tumor activity of celecoxib 79 and troglitazone, a peroxisome proliferatoractivated receptor γ (PPARγ) agonist that induces apoptosis in several cancers 177 . This information will help prioritize cancers for mechanistic studies and preclinical assessments of new compounds targeting proline enzymes.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…High Pro levels protect cancer cells from oxidative stress during oncogenesis. Pro has antioxidant activity that suppresses the production of ROS [ 15 , 69 , 70 ]. It has been reported that overexpressing ProDH/Pox reduces cellular Pro levels but increased ROS.…”
Section: Common Mechanisms Associated With Pro- Gln- Asn- and Arg-mentioning
confidence: 99%
“…The mechanism of the chemopreventive effect of celecoxib is not fully understood. Our previous research shows that this drug modulates proline metabolism in oral squamous cells leading to induction of apoptosis [ 5 ]. Breast cancer is a leading cause of death in women based on GLOBOCAN reports [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism of switching the PRODH/POX function between introducing cells into the autophagy or apoptosis needs further investigation. It was reported that cancer cells accumulate proline in higher concentrations than healthy cells providing substrate for PRODH/POX activity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%